Estimation of the structural integrity of a runway repaired by compliant polymer concretes under thermomechanical loading conditions. (15th April 2016) - Jung, Kyung-Chae; Chang, Seung-Hwan
Abstract: When repair materials are applied for runway maintenance, possible material failures due to the differences in material properties and excessive shrinkage of the repair material needs to be investigated. Moreover, the repair part is subjected to various mechanical loadings, which should be taken into account for determining the best repair material. In this study, we investigate a real-time in-situ health monitoring system, which is composed of two Fiber Bragg Grating (FBG) optic sensors, to monitor the strain variations that are induced by environmental conditions and material shrinkage. The repair process with compliant polymer concrete (72:20:08(T)) was carried out at the Gimpo international airport (Korea) during the summer season. To consider the effect of mechanical loading on stress distribution in the materials, several dynamic analyses are also carried out by using the finite element analysis method. Based on the results, the feasibility and reliability of the health monitoring system using FBG optic sensors are verified.